PENGARUH SERVANT LEADERSHIP TERHADAP MUTU LAYANAN PENDIDIKAN DI MTS. MIFTAAHUSH SHUDUUR KECAMATAN CIAMPEA KABUPATEN BOGOR - Nurmansah, Seno Aji; Awaludin S., Muhamad Robie; Abidin, Zaenal (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2023)
The quality of educational services is defined as the capacity of educational institutions to produce graduates with expertise and competencies organized systematically from input, process, to output. This research aims to: 1) Describe the concept of servant leadership at MTs. Miftaahush Shuduur, 2) Depict the quality of educational services at MTs. Miftaahush Shuduur, and 3) Analyze the impact of servant leadership on the quality of educational services at MTs. Miftaahush Shuduur. The study was conducted at MTs Miftaahush Shuduur in Ciampea District, Bogor Regency. The analysis results indicate that servant leadership positively affects the quality of educational services. This implies that the stronger the servant leadership, the higher the quality of educational services provided by the institution. Hence, to enhance the quality of educational services, greater emphasis on servant leadership is recommended.